Combined surgery and radiotherapy as curative treatment for tracheal adenoid cystic carcinoma: a case report - Gian Paolo Spinelli; Evelina Miele; Alessandra Anna Prete; Giuseppe Lo Russo; Alessandro Di Marzo; Claudio Di Cristofano; Silverio Tomao (Journal of Medical Case Reports, 2019)
Abstract Background Adenoid cystic carcinoma of the trachea is a rare tumor, characterized by slow growth and low rate of local and distant metastasis. When achievable, complete surgical resection represents the optimal treatment approach, with the highest results in terms of overall survival. Radiation therapy is a reasonable alternative in cases of inoperable disease. Case presentation We report a case of an 82-year-old white man affected by primary adenoid cystic carcinoma of the trachea, treated with debulking surgery and radiotherapy on the residual disease. A three-dimensional conformal radiation therapy was conducted. The total dose amounted to 70 Gy, administered in 35 fractions of 2 Gy. The medium doses given to the esophagus and lungs were 23 Gy and 4.2 Gy respectively. The maximum dose delivered to the spinal cord was 31 Gy with satisfactory results in terms of local control of the disease. Conclusion A combined approach of surgical resection followed by radiotherapy on the residual disease provided an excellent result in terms of disease control, quality of life, and overall survival in a patient with locally advanced tracheal adenoid cystic carcinoma.